The Role of Minimally Invasive Spine Surgery - Dahlan, Rully Hanafi; Ompusunggu, Sevline Estethia; Ade, Christian; Raharjo, Ayu Iswandari (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2020)
Introduction :In the past half of century, the spinal surgery techniques has advanced significantly. Along with the improvement and various of techniques and technologies in general, there has been a big movement to reduce the morbidity of surgery. Case review : As opposed to open spine surgery, minimally invasive surgical approaches can be faster, safer and require less recovery time. The minimally invasive spine surgery also need to make an efficient target of surgery. The roots in minimally invasive spine surgery (MISS) are based primarily on technique modifications. Discussion: The Williams microdiscectomy, described in 1978, revolutionized MISS by starting the evolution of lumbar discectomy from an open surgery through a 6-inch incision to a microsurgical approach through as small an opening as possible. Conclusion :We don’t use the MISS technique when the extension of tumor is more than 2 levels; extension of the tumor is 20% longer than diameter of largest retractor; the tumor > 3cm for interlaminary approach, the wide durotomy is needed; and also the case with intramedullary tumor with 80% extention, from left to the right side; en bloc as the the goal of surgery for extradural tumor